Melatonin in cryodiluent improves post-thaw quality andfertility of Murrah buffalo (Bubalus bubalis) bull spermatozoa - SINGH, P; SINGH, A K; DEVI, P; KUMAR, A; SINGH, N; RATTA, N S; SINGH, P (The Indian Journal of Animal Sciences, 2026)
The current research aimed to analyze the role of melatonin supplementation (0, 0.25, 0.5, 0.75 and 1.0 mM) on the freezability of buffalo bull spermatozoa. Thirty-six ejaculates were collected from six healthy bulls using artificial vagina. Only ejaculates with ≥70% progressive motility, ≤20% morphological defects and >500 million/ mL sperm concentration were selected for the study. Each ejaculate was diluted in Tris-egg yolk cryodiluent with selected concentrations of melatonin along with control and cryopreserved following established protocol. The post-thaw semen was assessed for sperm attributes and lipid peroxidation (LPO). IBM SPSS 22.0 software was used for statistical evaluations. The sperm total and progressive motility in post-thaw semen were evaluated using computer assisted semen analyzer (CASA) and were higher (P